Cinemagraphs “No Mundo-Tela” : entre o estático e o movimento - Barrero, Rodrigo de Morais (My University, 2019)
This project presents as it subject the cinemagraphs, a picture format that combines elements from cinema, photography and the GIF. The goal of this project is to explore the meaning of the movement within the cinemagraph image through the production of cinemagraphs and it’s exhibition in the “No Mundo-Tela”. The question that guides this project is “what is the meaning that movement in thecinemagraph can add to a photography?”. The project approaches the movement in photography since it’s principle until the creation of the cinemagraph. Also, it is aproached the creation process of the images produced. The conclusion is that the movement in the cinemagraph has no meaning on it’s own. For that, it is necessary to contextualize and think the movement within the limitations of the cinemagraph (sic).
Este projeto apresenta como tema as imagens cinemagraph, que mesclam elementos do cinema, da fotografia e do GIF. O objetivo desse projeto é explorar o sentido do movimento dentro da imagem cinemagraph através da produção de um ensaio utilizando o formato e a exibição do mesmo na exposição “No Mundo-Tela”. A questão norteadora desse projeto é “qual o significado que o movimento da técnica cinemagraph pode trazer dentro de uma imagem fotográfica?”. O projeto aborda o movimento na fotografia desde seus primórdios até a criação do cinemagraph. Também, é abordado o processo de concepção das imagens expostas. A conclusão é que o movimento no cinemagraph não é portador de sentido por si só, sendo necessário contextualizá-lo e concebê-lo dentro das limitações do cinemagraph (sic).
Keywords: Fotografia; Cinema; Movimento